2010
DOI: 10.1111/j.1600-0668.2010.00694.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension with elevated levels of oxidized low-density lipoprotein and anticardiolipin antibody in the circulation of premenopausal Indian women chronically exposed to biomass smoke during cooking

Abstract: The study showing high risk of developing cardiovascular diseases (CVD) among poor, underprivileged women in their reproductive ages in rural India is important from public health perspectives. It may motivate the government and the regulatory agencies of the country to take a serious note of the indoor air pollution (IAP) from biomass fuel use as it threatens the health of millions of women, children, and the elderly who mostly stay indoor. We hope the findings will strengthen the demand for setting up a stan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
58
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(63 citation statements)
references
References 69 publications
5
58
0
Order By: Relevance
“…The possible reasons for this slight difference may be attributed to the difference of study area, sample size, and the classification of solid fuel use. Furthermore, previous studies also found that the prevalence odds of hypertension for biomass users was 1.51 (95 % CI 1.14-2.08) times higher than LPG users among rural women, which can be considered as a support evidence for our results (Dutta et al 2011;Dutta and Ray 2012). Besides, it is also observed that longer duration of solid fuel use was associated with larger elevated SBP and DBP.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…The possible reasons for this slight difference may be attributed to the difference of study area, sample size, and the classification of solid fuel use. Furthermore, previous studies also found that the prevalence odds of hypertension for biomass users was 1.51 (95 % CI 1.14-2.08) times higher than LPG users among rural women, which can be considered as a support evidence for our results (Dutta et al 2011;Dutta and Ray 2012). Besides, it is also observed that longer duration of solid fuel use was associated with larger elevated SBP and DBP.…”
Section: Discussionsupporting
confidence: 74%
“…In a cross-sectional study in Putuo, an urban city of Shanghai in China, household solid fuel use was linked to higher prevalence odds of hypertension and the potential risk of hypertension increased with the duration of in-home solid fuel use (Lee et al 2012). Dutta et al (2011) and Dutta and Ray (2012) also found that the prevalence of hypertension was higher in biomass user than liquid petroleum gas (LPG) users in rural India.…”
Section: Introductionmentioning
confidence: 93%
“…Principally, the mechanisms involve increases in oxidative stress, lung-mediated inflammation and stimulation of the autonomic nervous system 40. Despite a paucity of controlled studies in the field of biomass fuel smoke exposure in humans, recent studies have demonstrated that exposure is associated with increased airway inflammation,16 serum amyloid A,15 inflammatory cytokines, circulating neutrophils,17 oxidised LDL particles and reactive oxygen species,11 all of which are associated with the development of atherosclerosis. Intriguingly, however, the biomass fuel group in our study actually demonstrated less inflammation (lower hsCRP) than those in the clean fuel group.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier studies have linked IAP from BMF with upregulation of ribosome biogenesis [36,37], inappropriate response of DNA damage repair proteins in the face of increased DNA damage [38,39], overactivation of signal transduction pathway involving Akt, i.e., protein kinase B [40], and hypertension with elevated levels of oxidized low-density lipoprotein indicating cardiovascular disease [41]. These findings along with observations from other studies led us to hypothesize that chronic exposure to IAP from biomass burning could be associated with neutrophilic inflammatory responses and oxidative stress in premenopausal women of rural India who cook regularly with BMF.…”
Section: Introductionmentioning
confidence: 99%